Place attachment, residential satisfaction, and life satisfaction: Traditional and renewed kibbutz. Issue 7 (3rd October 2017) - Casakin, Hernan; Reizer, Abira
ABSTRACT: Economic crisis in the early 1980s, followed by heavy debt, challenged the existence of the kibbutz. In order to prevent disintegration, rigorous privatization-related economic and structural reforms were implemented. In this study, we evaluate if these transformational changes affected the perception and emotional ties of kibbutz members. Specifically, we examined differences between traditional and renewed kibbutz in terms of life satisfaction, place attachment, and residential satisfaction. The results indicated that members of the renewed kibbutz reported higher levels of place attachment than those of the traditional kibbutz. However, no significant differences were observed for residential satisfaction and life satisfaction. Moreover, place attachment and residential satisfaction were significantly associated with life satisfaction. Finally, kibbutz type moderated the indirect effect of residential satisfaction on life satisfaction through place attachment.